ILUSI UANG: PENGARUH JUMLAH NOL PADA TAMPILAN HARGA TERHADAP WILLINGNESS TO PAY - Sidiq Maulana Muda; Erita Narhetali; Bertina Sjabadhyni (MANASA, 2012)
In the future, the government of Indonesia will launch the redenomination policy that cut the number of zeros of the Rupiah currency into three-digit. This study attempted to look at the effect of reducing the number of zeros in which will be displayed in price tags. The money illusion were measured through the willingness to pay (WTP) score. Participants are students of the Faculty of Psychology Syarif Hidayatullah State Islamic University of Jakarta (N = 136). The results of this study found that there are effects of the number of zeros onto the WTP (F (3.132) = 3.235, p